Significance of Kampo, Traditional Japanese Medicine, in Supportive Care of Cancer Patients. (19th June 2013) - Yamakawa, Jun-ichi; Motoo, Yoshiharu; Moriya, Junji; Ogawa, Masao; Uenishi, Hiroaki; Akazawa, Sumiyo; Sasagawa, Toshiyuki; Nishio, Matomo; Kobayashi, Junji
Abstract : The current standard treatment for cancer is a multidisciplinary therapy whereby various types of treatment are properly combined. Chemotherapy with multiple anticancer drugs is now common, and traditional, complementary, and alternative therapies are adopted as supportive measures. Medical care in Japan is distinguished by the ability for patients to access both Western and Kampo medical cares at the same time. There is a high degree of trust in the safety of Kampo therapies because they are practiced by medical doctors who are educated with fundamental diagnosis of Western medicine. Highly reliable clinical studies are being published, demonstrating that palliative or supportive care for cancer patients using Kampo preparations alleviates adverse effects of chemotherapy or radiotherapy. This paper reports the circumstances around cancer care in Japan where traditional therapeutic Kampo formulas are used for patients undergoing cancer treatment with cutting-edge chemotherapy, specifically to alleviate adverse effects of anticancer drugs.